Development Of New Toolkits For Orbit Determination Codes For Precise Radio Tracking Experiments - Zannoni, Marco <1985> (Alma Mater Studiorum - Università di Bologna, 2014)
This thesis describes the developments of new models and toolkits for the orbit determination codes to support and improve the precise radio tracking experiments of the Cassini-Huygens mission, an interplanetary mission to study the Saturn system.